Analysis of the combustion process in a lean-burning turbulent jet ignition engine fueled with methane. (1st November 2020) - Distaso, Elia; Amirante, Riccardo; Cassone, Egidio; De Palma, Pietro; Sementa, Paolo; Tamburrano, Paolo; Vaglieco, Bianca Maria
Highlights: A Turbulent Jet Ignition system was thoroughly analyzed by means of 3D numerical simulations. A separated analysis of the pre-chamber and the cylinder was performed. A faster and more efficient combustion than a conventional spark-ignition engine was obtained. The energy provided by the pre-chamber for the main charge ignition was quantified. Engine performance and pollutant emissions were assessed. Abstract: Recent needs of reducing pollutant emissions of internal combustion engines have pushed the development of non-conventional ignition systems. One of the most promising techniques appears to be the so-called Turbulent Jet Ignition (TJI) system, in which a jet of high-energy reactive gases is generated by means of a pilot combustion in a pre-chamber and used to initiate the main combustion event in the cylinder. Considering the complex nature of some phenomena typical of TJI systems, 3D CFD studies are essential to provide a detailed analysis for an efficient design. In this study, numerical simulations of an active pre-chamber TJI system applied to a lean operating methane engine were performed to provide a thorough analysis of the combustion process that characterizes such a technology. The numerical model was validated against experimental measurements carried out on an optically accessible single cylinder spark-ignition engine equipped with the pre-chamber prototype. The numerical simulations provided an insight view of both physical and chemical phenomena occurring inside the pre-chamber otherwise difficult to achieve by experiments alone. The evolution of some species of interest was analyzed in order to study the main charge ignition process, as well as the overall combustion progress. The results show that the main charge ignition is made possible by the large amount of energy and active radicals released from the pre-chamber and this ensures an overall stable and faster combustion in lean conditions. The performance improvements of the TJI system with respect to a traditional spark-ignition engine were evaluated in terms of efficiency and pollutant emission levels.